Strategi UMKM Bantul Merespon Pandemi (Studi Kasus Bidang Kriya/Kerajinan) - Suharson, Arif (Badan Perencanaan Pembangunan Daerah Kabupaten Bantul, 2020)
The purpose of this study is so that the msme bantul actors in the field of craft have a strategy to respond to pandemis by still doing activities, changing the way of view, and breaking the cross-border creation of products related to pandemis. The ease of access to information technology becomes a solution as a means of communication by utilizing the world of social media, developing professionalism and conducting collaborative synergies of mutually beneficial businesses. This study uses a qualitative paradigm with phenomenological approaches to conduct research and understanding processes based on methodologies that investigate a social phenomenon and human problems. This study uses a combination of several data collection techniques, namely: observation, interview, and documentation. Observations and interviews are conducted with population and sampling techniques. The method of data analysis used is a method of qualitative analysis presented descriptively. The results of the study get a complex picture of the impact of covid-19 pandemi on MSMEs in the field of craft, especially in Bantul Regency as the center of the most craft actors in Yogyakarta. The creative process of MSMEs in responding to the Covid-19 pandemi to stay afloat in difficult conditions has a major impact on the survival of MSMEs that impacts the widespread absorption of labor.